2020
DOI: 10.22207/jpam.14.2.08
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Evaluation of Anti-Bacterial, Anti-biofilm and Cytotoxic Activity of Naturally Inspired Juglans regia, Tamarix aphylla L., and Acacia modesta with Medicinal Potentialities

Abstract: The usefulness of medicinal plants has evoked increasing research interests to combat antimicrobial resistance. The current work reports on the in vitro bioactive activities, i.e., antibacterial, anti-biofilm and cytotoxicity evaluation of three medicinal plants. Extracts from different plant parts (leaves, stems, and root barks) were obtained using different solvents, such as methanol, ethanol, and water. The methanolic extracts of bark of Juglans regia and Tamarix aphylla L., whereas the stem of Acacia modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…T. aphylla bark extract exhibited 3.48 ± 1.08 hemolytic activity compared to the positive control. The studied T. aphylla extracts had a lower hemolytic potential, making them safe in pharmaceutical applications [ 142 ]. Many studies reported a high content of polyphenols, tannins, and flavonoids [ 143 , 144 , 145 ].…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 99%
“…T. aphylla bark extract exhibited 3.48 ± 1.08 hemolytic activity compared to the positive control. The studied T. aphylla extracts had a lower hemolytic potential, making them safe in pharmaceutical applications [ 142 ]. Many studies reported a high content of polyphenols, tannins, and flavonoids [ 143 , 144 , 145 ].…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 99%
“…As an adaption of bacteria that cause infection to withstand antibiotics, the possibility for antimicrobial resistance to cause a global health crisis emerges large 3,7 . This issue has led the need for the development of new medicines.…”
Section: Discussionmentioning
confidence: 99%
“…The demand is driven recently to use alternatives natural compounds instead of chemical ones such as plant extracts from medicinal and aromatic plants in addition to wild plants in defending diseases caused by different microbes fungal, bacterial, viral, nematode and insect 1,2 . The inclination towards the use of natural materials as a substitute for the artificial ones has increased dramatically due to some consequences of the latter such as undesirable side effects, complexity, the emergence of the medicine resistance trait and cost benefits, competition by manufacturers [3][4][5][6][7] . Many…”
Section: Introductionmentioning
confidence: 99%